Interaction between lower and upper tropical tropospheres during the southwest monsoon season over India - GEORGE, C. A (MAUSAM, 1970)
Raman and Ramanathan’s suggestion that latent heat released by "excessive cloudiness and copious precipitation" speeds up upper tropospheric winds over the west coast of India during the southwest monsoon is not borne out by observational evidence. Their proposition is shown to support rather than contradict Koteswaram’s hypothesis regarding upper tropospheric easterlies and the southwest monsoon activity along the west coast of India. The influence of these easterlies on the onset of monsoon over Kerala is illustrated for the year 1961-68.